PROGRAM APLIKASI TRAVELLING SALESMAN PADA PENDISTRIBUSIAN AGEN MINUMAN RINGAN MENGGUNAKAN TURBO PASCAL 7.1 - Yushi Nurdini (Faktor Exacta, 2011)
The Economic Crisis that still continues, causing many companies should lay off their employees. In order to survive they become drinks agents with the capital that they get from their severance pay. For the baverage producers it will become an apportunities to gain a huge advantage. But if there is a long distance between the subscribers it will become a big issue that should be solved it can makes the operational cost getting bigger. This writing explains the process to get the shortest path between the subscribers. Besides it will minimize delivery time, it also minimizes the operational cost. To design an application, I read pascal books as reference and I use pascal programming language Turbo Pascal 7.1 to make a simple application. Key Words: employees, distribution, cost, turbo pascal.